2017
DOI: 10.1038/s41598-017-12519-9
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the assembly and function of antibody variable domains

Abstract: The antibody Fv module which binds antigen consists of the variable domains VL and VH. These exhibit a conserved ß-sheet structure and comprise highly variable loops (CDRs). Little is known about the contributions of the framework residues and CDRs to their association. We exchanged conserved interface residues as well as CDR loops and tested the effects on two Fvs interacting with moderate affinities (KDs of ~2.5 µM and ~6 µM). While for the rather instable domains, almost all mutations had a negative effect,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 55 publications
(87 reference statements)
0
16
0
Order By: Relevance
“…To support the development of a particular bispecific antibody, a strong scientific rationale should be provided including, but not limited to, adequate description of the two targets and the rationale for bispecific targeting [mechanism-of-action (MOA)], dose rationale and increased safety and/or efficacy as compared to similar monospecific products and available therapies. Diverse formats and engineering strategies enabling the design of BsAbs supporting a proposed MOA and the intended clinical application may also cause (1) unexpected attribute changes in BsAbs such as immunogenicity, antigen specificity, affinity and half-life or (2) production-related challenges including production yield, process-related impurities and stability (Atwell et al 1997 ; Chailyan et al 2011 ; Herold et al 2017 ; Masuda et al 2006 ). Different formats of BsAbs may require unique development considerations or technologies for each of them, but eventually, the BsAb products should be developed in accordance with standard monoclonal antibody development practices posing new challenges to CMC.…”
Section: Challenges and Considerations For The Development Of Dual Tamentioning
confidence: 99%
“…To support the development of a particular bispecific antibody, a strong scientific rationale should be provided including, but not limited to, adequate description of the two targets and the rationale for bispecific targeting [mechanism-of-action (MOA)], dose rationale and increased safety and/or efficacy as compared to similar monospecific products and available therapies. Diverse formats and engineering strategies enabling the design of BsAbs supporting a proposed MOA and the intended clinical application may also cause (1) unexpected attribute changes in BsAbs such as immunogenicity, antigen specificity, affinity and half-life or (2) production-related challenges including production yield, process-related impurities and stability (Atwell et al 1997 ; Chailyan et al 2011 ; Herold et al 2017 ; Masuda et al 2006 ). Different formats of BsAbs may require unique development considerations or technologies for each of them, but eventually, the BsAb products should be developed in accordance with standard monoclonal antibody development practices posing new challenges to CMC.…”
Section: Challenges and Considerations For The Development Of Dual Tamentioning
confidence: 99%
“…Overall, the binding of the antigen to EDE1 C8 Fab corresponded to a reduced mobility of the flexible CDR loops locking these loops in a distinct conformational state, and strong reduction of the mobility of these loops has also been observed in the past in cases of strong antigen–Fab binding …”
Section: Discussionmentioning
confidence: 87%
“…CDR loops are not only involved in antigen recognition, they have also been shown to play important structural roles in antibody domain architecture and V H /V L domain association. Various experimental and computational studies on V L domains demonstrated that CDRs can have a strong influence on the folding pathway, stability, and conformation of the protein ( 69 , 70 , 71 , 72 ). The involvement of a CDR mutation in LC amyloidogenicity has been shown for a proline residue in the CDR3 loop of an amyloidogenic V L domain.…”
Section: Discussionmentioning
confidence: 99%